The Lithium Battery: assessing the neurocognitive profile of lithium in bipolar disorder. (23rd March 2016) - Malhi, Gin S; McAulay, Claire; Gershon, Samuel; Gessler, Danielle; Fritz, Kristina; Das, Pritha; Outhred, Tim
Abstract : Objective: The aim of the present study was to characterize the neurocognitive effects of lithium in bipolar disorder to inform clinical and research approaches for further investigation. Methods: Key words pertaining to neurocognition in bipolar disorder and lithium treatment were used to search recognized databases to identify relevant literature. The authors also retrieved gray literature (e.g., book chapters) known to them and examined pertinent articles from bibliographies. Results: A limited number of studies have examined the effects of lithium on neurocognition in bipolar disorder and, although in some domains a consistent picture emerges, in many domains the findings are mixed. Lithium administration appears to reshape key components of neurocognition – in particular, psychomotor speed, verbal memory, and verbal fluency. Notably, it has a sophisticated neurocognitive profile, such that while lithium impairs neurocognition across some domains, it seemingly preserves others – possibly those vulnerable to the effects of bipolar disorder. Furthermore, its effects are likely to be direct and indirect (via mood, for example) and cumulative with duration of treatment. Disentangling the components of neurocognition modulated by lithium in the context of a fluctuating and complex illness such as bipolar disorder is a significant challenge but one that therefore demands a stratified and systematic approach, such as that provided by the Lithium Battery . Conclusions: In order to delineate the effects of lithium therapy on neurocognition in bipolar disorder within both research and clinical practice, a greater understanding and measurement of the relatively stable neurocognitive components is needed to examine those that indeed change with lithium treatment. In order to achieve this, we propose a Lithium Battery – Clinical and a Lithium Battery – Research that can be applied to these respective settings.